Insight into the photosynthetic apparatus in evergreen and deciduous European oaks during autumn senescence using OJIP fluorescence transient analysis - Holland, V; Koller, S; Brüggemann, W (Plant Biology, 2014)
Climate change is one of the major issues nowadays, and Mediterranean broadleaf species have been suggested to fill possible future gaps created by climate change in Central European forests. To provide a scientific-based foundation for such practical strategies, it is important to obtain a general idea about differences and similarities in the physiology of Central European and Mediterranean species. In the present study, we evaluated the onset of leaf senescence of a broad spectrum of oak species under the Central European climate in a common garden experiment. Degradation of the photosynthetic apparatus of evergreen (Quercus ilex, Q. suber), semi-evergreen (Q. × turneri, Q. × hispanica) and deciduous oaks (Q. robur, Q. cerris, Q. frainetto, Q. pubescens) was monitored as chlorophyll content and analysed chlorophyll fluorescence induction transients. In the deciduous species, a significant decline in chlorophyll content was observed during autumn/winter, with Q. pubescens showing the slowest decline. Analysis of fluorescence induction transients revealed a significant decline in quantum efficiency of the primary photochemistry and reaction centre density and later, a decrease in quantum efficiency of end acceptor reduction. Alterations in fluorescence parameters were compared to the decline in chlorophyll content, which occurred much more slowly than expected from the fluorescence data. The evergreen species showed no decline in chlorophyll content, nor different chlorophyll a fluorescence induction behaviour despite temperature falling below 0 °C. The hybrids showed intermediate behaviour between their parental evergreen and deciduous taxa.
Keywords: chlorophyll fluorescence; climate change; portable fluorimeter; Quercus; Senescence; SPAD

Light transmissivity of tube shelters affects root growth and biomass allocation of Quercus ilex L. and Pinus halepensis Mill - de Castro, Alberto Vázquez; Oliet, Juan A.; Puértolas, Jaime; Jacobs, Douglass F.; Puértolas, Jaime; Jacobs, Douglass F. (ANNALS OF FOREST SCIENCE, 2014)
Context Tube shelters have been shown to enhance field performance of several Mediterranean species, but responses of newly planted seedlings to the microenvironment induced by shelter walls with different light transmissivity are still poorly documented. Aims We studied effects of a range of shelters with varying light transmissivity on post-planting seedling responses during the wet season establishment phase for two Mediterranean trees of contrasting functional ecology. Methods Root growth, biomass allocation, water potential, and chlorophyll fluorescence of Quercus ilex and Pinus halepensis seedlings were evaluated across shelters varying in light transmissivity (80, 40, 20, and 10 % plus a mesh shelter) with irrigation. Results Plants in dark tubes (20 and 10 % light transmissivity) had less above-and belowground growth and more than two times greater leaf to protruding roots mass ratio, with shoot growth response of Q. ilex being less plastic. Ratio of leaf area/protruding roots area decreased when light transmissivity increased, although no differences were found at >= 40 % transmissivity. Xylem water potential indicated lack of water stress, and high maximum photosynthetic efficiency (F-v/F-m) values show no photoinhibition symptoms irrespective of light transmissivity. Conclusion Shelter transmissivity >= 40 % promotes rapid and vigorous root growth immediately after planting for these species. This minimum transmissivity should be considered as a target when designing shelters to help root development and improve water balance of Mediterranean seedlings.
Keywords: Aleppo pine; chlorophyll fluorescence; Forest restoration; Holm oak; Light ambient response; Mediterranean climate; Transplanting performance; Treeshelters

Frost-acclimation of photosynthesis in overwintering Mediterranean holm oak, grown in Central Europe - Pflug, Ellen; Brüggemann, Wolfgang (International Journal of Plant Biology, 2012)
As a consequence of global change, forestry in Central Europe has to expect and be prepared for an increase of hot and dry summers in the near future. In two model plantations of the Mediterranean holm oak (Quercus ilex L.) in Central Europe (Rhine-Main basin) we tested its potential as a future forestry tree for drought-threatened stands by studying its overwintering strategy under harsh winter conditions. During prolonged frost periods, chronic photoinhibition was developed, which lasted until the end of the frost period. Nearly all plants survived minimum temperatures of - 16 to -18°C and their photosynthetic apparatus recovered completely during late winter. A detailed study of the temperature dependence of chlorophyll (chl) fluorescence parameters of the OJIP test revealed statistically significant correlations between minimum temperature and maximum quantum yield of primary photochemistry (Fv/Fm), absorption rate/reaction centre (ABS/RC), dissipation rate/reaction centre (DI0/RC) and electron transport rate/reaction centre (ET0/RC) as well as with the deepoxidation state (DES) of the xanthophyll pigments. The DES correlated with Fv/Fm, ABS/RC, DI0/RC and ET0/RC. It is concluded, that from the point of view of the winter hardiness of the photosynthetic apparatus, Q. ilex should be further investigated as a potential future forestry tree also for very dry and warm stands in Central Europe under the scenarios of climate change.
Keywords: chlorophyll fluorescence; ojip test; xanthophyll cycle

Impact of the Mediterranean Urban Environment on Photosynthetic Efficiency of Quercus ilex Leaves - De Nicola, Flavia; Alfani, Anna; D’Ambrosio, Nicola (Water, Air, & Soil Pollution, 2011)
Environmental constrains and anthropogenic changes can contribute simultaneously to the limitation of plant performance in Mediterranean urban areas. Photosynthetic efficiency of Quercus ilex L. leaves from the urban area of Naples was evaluated by comparison with leaves from remote site (Vesuvius National Park). The photosynthetic performance of leaves with different age (current year [CY], 1- [1Y] and 2-year old [2Y]) was assessed by measurements of gas exchange, chlorophyll fluorescence and pigment contents. The photosynthetic activity at the urban site was higher than that at the remote site for the CY leaves, while the opposite was observed for the 1Y and 2Y leaves. The growth of Q. ilex trees was mainly sustained by the CY leaves at the urban site, whereas at the remote site the photosynthetic activity was not affected by leaf ageing. In the urban environment, Q. ilex leaves strongly decreased the photosynthetic performance with leaf ageing as highlighted by leaf gas exchanges, although the photochemistry did not show any significant change. The mature leaves of urban site drove the reductive power deriving from the photochemistry more in nonassimilative processes rather than in carbon assimilative ones, avoiding a strong decrease of PSII photochemical efficiency
Keywords: chlorophyll fluorescence; environmental stress; leaf ageing; leaf gas exchange; photosynthetic pigments; urban; urban environmental stress

Facilitation of Quercus ilex in Mediterranean shrubland is explained by both direct and indirect interactions mediated by herbs - Cuesta, Bárbara; Villar-Salvador, Pedro; Puértolas, Jaime; Rey Benayas, José M.; Michalet, Richard (Journal of Ecology, 2010)
1. Competitive and facilitative interactions shape plant communities. Whereas a number of studies have addressed competition and direct facilitation among plants in dry ecosystems, indirect facilitation has received little attention. 2. We investigated the relative importance of direct and indirect facilitation by the nurse plant Retama sphaerocarpa on late-successional Quercus ilex seedlings mediated by herb suppression in a Mediterranean shrubland in 2006 and 2007. We also studied whether facilitation outcome depended on the size of the facilitated seedlings. 3. A field experiment was carried out to test the effect of (i) position of Q. ilex seedling with respect to shrub canopy (under shrubs or in gaps), (ii) herb competition (presence or absence), and (iii) seedling size. 2006 was an average rainfall year while 2007 had a much more humid spring and a dryer summer than 2006. 4. In both years, nurse shrubs reduced seedling mortality whereas herbs increased it. In the average rainfall year, seedling mortality under shrubs was unaffected by herbs whereas in gaps it was significantly higher in presence of herbs. This showed that the nurse shrub indirectly facilitated the seedlings by reducing the competitive capacity of herbs. Conversely, facilitation was predominately direct during the humid spring and dry summer year since herbs hindered seedling survival similarly under the nurse shrub and in gaps. The nurse shrub directly facilitated the seedlings by reducing seedling photoinhibition and water stress. 5. Improvement of environmental conditions by Retama benefited smaller seedlings but not larger seedlings since the nurse shrub reduced mortality of smaller seedlings relative to that in gaps, but this effect was not observed for larger seedlings. This indicates that individuals within a seedling population may not have the same response to facilitation. 6. Synthesis. Both indirect and direct facilitation are important mechanisms for Q. ilex regeneration in Retama shrubland and their importance seems to vary with climatic conditions. Indirect facilitation by release of herb competition under nurse shrubs is important in years of dry springs when competition between nurse shrubs and herbs is high, whereas direct facilitation mediated by microclimate amelioration increases with summer aridity.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: chlorophyll fluorescence; herb competition; Quercus ilex; retama sphaerocarpa; seedling size; water potential

THE INFLUENCE OF FERTILISATION ON SALT (SODIUM CHLORIDE) DAMAGE IN TRANSPLANTED SCOTS PINE (PINUS SYLVESTRIS) AND EVERGREEN OAK (QUERCUS ILEX) - Beis, Vassilios K.; Percival, Glynn C. (Arboricultural Journal, 2009)
Summary The aim of this study was to determine the influence of a range of commercially available fertilisers on tree responses following salt (sodium chloride) damage to foliar tissue of containerized evergreen oak (Quercus ilex) and Scots pine (Pinus sylvestris). Evergreen oak proved to be more salt tolerant than Scots pine. Tree responses to fertilisation following 6% foliar salt spray were measured by chlorophyll fluorescence, photosynthetic rates, leaf chlorophyll content, leaf necrosis and leaf sodium and chloride concentrations over a nine week period. Tree responses were 20?300% higher in fertilised compared to nonfertilised trees, irrespective of species. In all cases non-fertilised trees had the least capacity to respond positively following salt damage. In addition leaf area, shoot, root, total plant dry weight was higher in fertilised trees compared to non-fertilised ones at the end of a nineweek period. Results of this investigation indicate applications of commercially available fertilisers would be of benefit to induce positive tree response rates and subsequent growth following sodium chloride damage to foliar tissue. Selection of an appropriate fertiliser, however, is important as effects on growth and vitality varied widely depending on the type of fertiliser applied.
doi: 10.1080/03071375.2009.9747582doi: 10.1080/03071375.2009.9747582The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: chlorophyll fluorescence; Chlorophylls; photosynthesis; physiogenic stress; plant health care; stress tolerance

Leaf flavonoid content in Quercus ilex L. resprouts and its seasonal variation - Brossa, R.; Casals, I.; Pintó-Marijuan, M.; Fleck, I. (Trees, 2008)
Here, we provide the ﬁrst report on ﬂavonoid content in holm oak (Quercus ilex L.) leaves, analyzed by HPLC–MS/MS. Flavanols and ﬂavonols were the predominant groups, although proanthocyanidins and many soluble tannins had a relevant presence in all leaf samples. Seasonal variation of ﬂavonoids was determined in extracts from Q. ilex leaves during resprouting after a forest ﬁre in two Mediterranean forests. Similar seasonal trends were observed over 2 years during the two main stress seasons (winter and summer). The most abundant ﬂavonoid was the ﬂavanol epicatechin, which showed similar values during the two seasons. Hexosides of the ﬂavonols, quercetin, kaempferol and rhamnetin showed considerably higher content in winter, especially at the lowest temperatures. These variations in both forests are discussed on the basis of the chlorophyll ﬂuorescence results obtained. Anthocyanins were found practically absent in mature leaves. Nutrient or water availability differences between sites or seasons were not related to changes in leaf ﬂavonolhexoside content.
Keywords: á; á hplc; chlorophyll fluorescence; chlorophyll fluorescence á flavanols; esi; flavanols; flavonol-hexosides; flavonol-hexosides á holm oak; Holm oak; HPLC–ESI–MS/MS; ms

Leaf flavonoid content in Quercus ilex L. resprouts and its seasonal variation - Brossa, R.; Casals, I.; Pintó-Marijuan, M.; Fleck, I. (Trees, 2008)
Here, we provide the ﬁrst report on ﬂavonoid content in holm oak (Quercus ilex L.) leaves, analyzed by HPLC–MS/MS. Flavanols and ﬂavonols were the predominant groups, although proanthocyanidins and many soluble tannins had a relevant presence in all leaf samples. Seasonal variation of ﬂavonoids was determined in extracts from Q. ilex leaves during resprouting after a forest ﬁre in two Mediterranean forests. Similar seasonal trends were observed over 2 years during the two main stress seasons (winter and summer). The most abundant ﬂavonoid was the ﬂavanol epicatechin, which showed similar values during the two seasons. Hexosides of the ﬂavonols, quercetin, kaempferol and rhamnetin showed considerably higher content in winter, especially at the lowest temperatures. These variations in both forests are discussed on the basis of the chlorophyll ﬂuorescence results obtained. Anthocyanins were found practically absent in mature leaves. Nutrient or water availability differences between sites or seasons were not related to changes in leaf ﬂavonolhexoside content.
Keywords: á; á hplc; chlorophyll fluorescence; chlorophyll fluorescence á flavanols; esi; flavanols; flavonol-hexosides; flavonol-hexosides á holm oak; Holm oak; HPLC–ESI–MS/MS; ms

Comparative ecophysiological effects of drought on seedlings of the Mediterranean water-saver Pinus halepensis and water-spenders Quercus coccifera and Quercus ilex - Baquedano, F. J.; Castillo, F. J. (Trees, 2006)
Ecophysiological and structural traits of seedlings of the water-saver Pinus halepensis and the water-spenders Quercus coccifera and Q. ilex were studied in response to water stress under greenhouse conditions. Water deﬁcit reduced stomatal conductance (gs ) and, as a consequence, both net CO2 assimilation (A) and transpiration rate (E) were also reduced. Water stress also emphasized midday downregulation of the photochemical efﬁciency (dynamic photoinhibition) reducing quantum yield of noncyclic electron transport (PSII ), photochemical quenching (qP) and photochemical efﬁciency of the open reaction centres of PSII (F v /F m) and involved an increase of thermal dissipation of excess energy. However, water stress not only induced dynamic photoinhibition but also brought a reduction in Fv/Fm (chronic photoinhibition). Despite the water-saving strategy ofP. halepensisthat limited net CO2 assimilation, this species showed a higher photochemical efﬁciency and lower photoinhibition than Quercusspecies. This was not the result of a different photochemical quenching but was linked to a higher value of F v /F m, indicating a less severe photo-inactivation of PSII. Water stress resulted in a loss of pigment content and in an increase of the carotenoids/chlorophyll ratio, antioxidant capacity and the biomass rate allocated to roots as opposed to that assigned to leaves. P. halepensis showed a lower photoinhibition and antioxidant activity than Quercus species due to its lower pigment content and higher proportion of carotenoids allowing P. halepensis to use, in a more effective way, the lesser excess energy absorbed.
Keywords: antioxidant activity; chlorophyll fluorescence; gas exchange and water potential; morphological parameters; pigments

Comparative ecophysiological effects of drought on seedlings of the Mediterranean water-saver Pinus halepensis and water-spenders Quercus coccifera and Quercus ilex - Baquedano, F J; Castillo, F J (Trees, 2006)
Ecophysiological and structural traits of seedlings of the water-saver Pinus halepensis and the water-spenders Quercus coccifera and Q. ilex were studied in response to water stress under greenhouse conditions. Water deﬁcit reduced stomatal conductance (gs ) and, as a consequence, both net CO2 assimilation (A) and transpiration rate (E) were also reduced. Water stress also emphasized midday downregulation of the photochemical efﬁciency (dynamic photoinhibition) reducing quantum yield of noncyclic electron transport (PSII ), photochemical quenching (qP) and photochemical efﬁciency of the open reaction centres of PSII (F v /F m) and involved an increase of thermal dissipation of excess energy. However, water stress not only induced dynamic photoinhibition but also brought a reduction in Fv/Fm (chronic photoinhibition). Despite the water-saving strategy ofP. halepensisthat limited net CO2 assimilation, this species showed a higher photochemical efﬁciency and lower photoinhibition than Quercusspecies. This was not the result of a different photochemical quenching but was linked to a higher value of F v /F m, indicating a less severe photo-inactivation of PSII. Water stress resulted in a loss of pigment content and in an increase of the carotenoids/chlorophyll ratio, antioxidant capacity and the biomass rate allocated to roots as opposed to that assigned to leaves. P. halepensis showed a lower photoinhibition and antioxidant activity than Quercus species due to its lower pigment content and higher proportion of carotenoids allowing P. halepensis to use, in a more effective way, the lesser excess energy absorbed.
Keywords: antioxidant activity; chlorophyll fluorescence; gas exchange and water potential; morphological parameters; pigments

Seasonal changes in photosynthesis and photoprotection in a Quercus ilex subsp. ballota woodland located in its upper altitudinal extreme in the Iberian Peninsula - Corcuera, L; Morales, F; Abadía, A; Gil-Pelegrín, E (Tree Physiology, 2005)
Quercus ilex L. subsp. ballota (Desf.) Samp., a Mediterranean evergreen species growing in a continental Mediterranean climate, did not experience water stress and showed greater sensitivity to winter stress than to summer stress over a 12-month period. Net CO2 assimilation rates and photosystem II (PSII) efficiency decreased markedly during the cold months and recovered completely in spring. Lutein, neoxanthin and β-carotene to chlorophyll (Chl) molar ratios all showed the same trend throughout the year, increasing from September to March. This increase was a result of increases in carotenoid concentrations, because Chl concentration per unit leaf area remained stable, and was higher at the end than at the beginning of the first growing season. Lutein-epoxide was a minor component of the total lutein pool. Thermal energy dissipation and non-photochemical quenching (NPQ) were associated with the de-epoxidated forms of the xanthophyll cycle pigments in the warm months. Photosynthetic rates decreased slightly at midday in summer. These changes were accompanied by decreases in maximum potential PSII efficiency (which recovered during the night), actual and intrinsic PSII efficiencies, photochemical quenching and increases in NPQ. Overall, our data indicate down-regulation of photosynthesis during the summer. The diurnal de-epoxidation of violaxanthin to antheraxanthin and zeaxanthin occurred throughout the year, except in January. Antioxidant enzymatic activity increased in the winter months, especially during the coldest months, highlighting its key role in photoprotection against photo-oxidation. Structural and functional modifications protected PSII from permanent damage and allowed 1-year-old leaves to photosynthesize at high rates when temperatures increased in spring.
10.1093/treephys/25.5.599
Keywords: antioxidant enzymatic activity; chlorophyll fluorescence; photosynthetic pigments; summer stress; winter stress

Seasonal changes in photosynthesis and photoprotection in a Quercus ilex subsp. ballota woodland located in its upper altitudinal extreme in the Iberian Peninsula - Corcuera, L.; Morales, F.; Abadia, A.; GIL-PELEGRÍN, E. (Tree Physiology, 2005)
Quercus ilex L. subsp. ballota (Desf.) Samp., a Mediterranean evergreen species growing in a continental Mediterranean climate, did not experience water stress and showed greater sensitivity to winter stress than to summer stress over a 12-month period. Net CO2 assimilation rates and photosystem II (PSII) efficiency decreased markedly during the cold months and recovered completely in spring. Lutein, neoxanthin and β-carotene to chlorophyll (Chl) molar ratios all showed the same trend throughout the year, increasing from September to March. This increase was a result of increases in carotenoid concentrations, because Chl concentration per unit leaf area remained stable, and was higher at the end than at the beginning of the first growing season. Lutein-epoxide was a minor component of the total lutein pool. Thermal energy dissipation and non-photochemical quenching (NPQ) were associated with the de-epoxidated forms of the xanthophyll cycle pigments in the warm months. Photosynthetic rates decreased slightly at midday in summer. These changes were accompanied by decreases in maximum potential PSII efficiency (which recovered during the night), actual and intrinsic PSII efficiencies, photochemical quenching and increases in NPQ. Overall, our data indicate down-regulation of photosynthesis during the summer. The diurnal de-epoxidation of violaxanthin to antheraxanthin and zeaxanthin occurred throughout the year, except in January. Antioxidant enzymatic activity increased in the winter months, especially during the coldest months, highlighting its key role in photoprotection against photo-oxidation. Structural and functional modifications protected PSII from permanent damage and allowed 1-year-old leaves to photosynthesize at high rates when temperatures increased in spring.
10.1093/treephys/25.5.59910.1093/treephys/25.5.599
Keywords: antioxidant enzymatic activity; chlorophyll fluorescence; photosynthetic pigments; summer stress; winter stress

The effect of low temperatures on the photosynthetic apparatus of Quercus ilex subsp. ballota at its lower and upper altitudinal limits in the Iberian peninsula and during a single freezing-thawing cycle - Corcuera, L.; Morales, F.; Abadia, A.; GIL-PELEGRÍN, E. (Trees, 2004)
We investigated the response of the photosynthetic apparatus during an episode of extreme low winter temperature in Quercus ilex subsp. ballota (Desf.) Samp., a typical Mediterranean evergreen species in the Iberian peninsula. Both plants in a woodland located at high altitude (1,177 m. a.s.l.) and potted plants obtained from acorns of the same populations grown at low altitude (225 m. a.s.l.) were analyzed. Net CO2 assimilation rate was negative and there was a marked decrease in photosystem II (PSII) efficiency during winter in leaves of the woodland population (high altitude individuals). These processes were accompanied by increases in nonphotochemical quenching (NPQ) and in the de-epoxidated carotenoids within the xanthophyll cycle, mechanisms aimed to dissipate excess energy. In addition, these deepoxidated carotenoids were largely preserved during the night. There was no chlorophyll bleaching during the winter, which suggests that leaves were not experiencing photoinhibitory damage. In fact, the net photosynthetic rate and the PSII efficiency recovered in spring. These changes were not observed, or were much more reduced, in individuals located at lower altitude after a few frosts. When the response to rapid temperature changes (from 20°C to −5°C and from −5°C to 20°C) was studied, it was found that the maximum potential PSII efficiency was fairly stable, ranging from 0.70 to 0.75. The rest of the photosynthetic parameters measured, actual and intrinsic PSII efficiency, photochemical and NPQ, responded immediately to the changes in temperature and, also, the recovery after cold events was practically immediate.
Keywords: chlorophyll fluorescence; Holm oak; photochemical and non-photochemical quenching; photoprotection; photosystem ii efficiency

The effect of low temperatures on the photosynthetic apparatus of Quercus ilex subsp. ballota at its lower and upper altitudinal limits in the Iberian peninsula and during a single freezing-thawing cycle - Corcuera, L; Morales, F; Abadía, A; Gil-Pelegrín, E (Trees, 2004)
We investigated the response of the photosynthetic apparatus during an episode of extreme low winter temperature in Quercus ilex subsp. ballota (Desf.) Samp., a typical Mediterranean evergreen species in the Iberian peninsula. Both plants in a woodland located at high altitude (1,177 m. a.s.l.) and potted plants obtained from acorns of the same populations grown at low altitude (225 m. a.s.l.) were analyzed. Net CO2 assimilation rate was negative and there was a marked decrease in photosystem II (PSII) efficiency during winter in leaves of the woodland population (high altitude individuals). These processes were accompanied by increases in nonphotochemical quenching (NPQ) and in the de-epoxidated carotenoids within the xanthophyll cycle, mechanisms aimed to dissipate excess energy. In addition, these deepoxidated carotenoids were largely preserved during the night. There was no chlorophyll bleaching during the winter, which suggests that leaves were not experiencing photoinhibitory damage. In fact, the net photosynthetic rate and the PSII efficiency recovered in spring. These changes were not observed, or were much more reduced, in individuals located at lower altitude after a few frosts. When the response to rapid temperature changes (from 20°C to −5°C and from −5°C to 20°C) was studied, it was found that the maximum potential PSII efficiency was fairly stable, ranging from 0.70 to 0.75. The rest of the photosynthetic parameters measured, actual and intrinsic PSII efficiency, photochemical and NPQ, responded immediately to the changes in temperature and, also, the recovery after cold events was practically immediate.
Keywords: chlorophyll fluorescence; Holm oak; photochemical and non-photochemical quenching; photoprotection; photosystem ii efficiency

Thermal optima of photosynthetic functions and thermostability of photochemistry in cork oak seedlings - Ghouil, Hana; Montpied, Pierre; Epron, Daniel; Ksontini, Mustapha; Hanchi, Belkacem; Dreyer, Erwin (Tree Physiology, 2003)
Temperature effects on photosynthesis were studied in seedlings of evergreen Mediterranean cork oak (Quercus suber L.). Responses to changes in temperature and the temperature optima of maximal carboxylation rate (Vcmax) and maximal light-driven electron flux (Jmax) were estimated from gas exchange measurements and a leaf-level photosynthesis model. The estimated temperature optima were approximately 34 and 33 °C for Vcmax and Jmax, respectively, which fall within the lower range of temperature optima previously observed in deciduous tree species. The thermostability of the photosynthetic apparatus was estimated according to the temperature at which basal chlorophyll a fluorescence begins to increase (Tc). The Tc was highly variable, increasing from 42 to 51 °C when ambient temperature rose from 10 to 40 °C, and increasing from 44 to 54 °C with decreasing soil water availability while net CO2 assimilation rate dropped to almost zero. When a heat shock was imposed, an additional small increase in Tc was observed in drought-stressed and control seedlings. Maximal Tc values following heat shock were about 56 °C, which, to our knowledge, are the highest values that have been observed in tree species. In conclusion, the intrinsic temperature responses of cork oak did not differ from those of other species (similar Tc under ambient temperature and water availability, and relatively low thermal optima for photosynthetic capacity in seedlings grown at cool temperatures). However, the large ability of cork oak to acclimate to drought and elevated temperature may be an important factor in the tolerance of this evergreen Mediterranean species to summer drought and high temperatures.
10.1093/treephys/23.15.103110.1093/treephys/23.15.1031
Keywords: chlorophyll fluorescence; Gas exchange; maximal carboxylation rate; maximal light-driven electron flow; Regeneration

Thermal optima of photosynthetic functions and thermostability of photochemistry in cork oak seedlings - Ghouil, Hana; Montpied, Pierre; Epron, Daniel; Ksontini, Mustapha; Hanchi, Belkacem; Dreyer, Erwin (Tree Physiology, 2003)
Temperature effects on photosynthesis were studied in seedlings of evergreen Mediterranean cork oak (Quercus suber L.). Responses to changes in temperature and the temperature optima of maximal carboxylation rate (Vcmax) and maximal light-driven electron flux (Jmax) were estimated from gas exchange measurements and a leaf-level photosynthesis model. The estimated temperature optima were approximately 34 and 33 °C for Vcmax and Jmax, respectively, which fall within the lower range of temperature optima previously observed in deciduous tree species. The thermostability of the photosynthetic apparatus was estimated according to the temperature at which basal chlorophyll a fluorescence begins to increase (Tc). The Tc was highly variable, increasing from 42 to 51 °C when ambient temperature rose from 10 to 40 °C, and increasing from 44 to 54 °C with decreasing soil water availability while net CO2 assimilation rate dropped to almost zero. When a heat shock was imposed, an additional small increase in Tc was observed in drought-stressed and control seedlings. Maximal Tc values following heat shock were about 56 °C, which, to our knowledge, are the highest values that have been observed in tree species. In conclusion, the intrinsic temperature responses of cork oak did not differ from those of other species (similar Tc under ambient temperature and water availability, and relatively low thermal optima for photosynthetic capacity in seedlings grown at cool temperatures). However, the large ability of cork oak to acclimate to drought and elevated temperature may be an important factor in the tolerance of this evergreen Mediterranean species to summer drought and high temperatures.
10.1093/treephys/23.15.1031
Keywords: chlorophyll fluorescence; Gas exchange; maximal carboxylation rate; maximal light-driven electron flow; Regeneration

Photosynthetic responses to water deficit in six Mediterranean sclerophyll species: possible factors explaining the declining distribution of Rhamnus ludovici-salvatoris, an endemic Balearic species. - Gulías, J; Flexas, J; Abadía, A; Madrano, H (Tree Physiology, 2002)
We sought to explain the declining distribution in the Balearic Islands of the endemic shrub Rhamnus ludovici-salvatoris R. Chodat, by comparing its photosynthetic response to drought with that of several widely distributed, competing Mediterranean species (R. alaternus L., Quercus ilex L., Pistacia lentiscus L., Q. humilis Mill. and P. terebinthus L.). [ABSTRACT FROM PUBLISHER]
Keywords: chlorophyll fluorescence; deciduous; Drought; evergreen; Gas exchange; leaf mass area; nitrogen; Pistacia; Quercus; Rhamnus; xanthophyll cycle

Allocation of absorbed light energy into photochemistry and dissipation in a semi-deciduous and an evergreen Mediterranean woody species during winter - Oliveira, G; Penuelas, J (AUSTRALIAN JOURNAL OF PLANT PHYSIOLOGY, 2001)
The importance of photodissipation in the protection from excessive solar energy absorption during winter was evaluated in shrubs of Cistus albidus L. (semi-deciduous) and Quercus ilex L. (evergreen). Diurnal and seasonal changes in chlorophyll a (Chl a) fluorescence-related parameters of leaves with different microclimates (south- and north-facing leaves) were assessed from early winter to late spring in a Mediterranean plant community. Maximal photochemical efficiency of photosystem II (PSII) (F-v/F-m) was lowest on sunny and cold winter days, but low values on overcast (and cold) days indicated that the whole winter season was potentially stressful. Photoinhibition was greater in south than in north leaves during winter. There was a decreased proportion of absorbed light utilised in photochemistry, and an increase in that proportion diverted into dissipation processes on cold sunny days. Under low light conditions (e.g. of north-facing leaves throughout the winter, or all the canopy on overcast days), a greater proportion of light energy was allocated to photochemistry than in bright conditions, although still smaller than the dissipated fraction. Allocation to photochemistry prevailed over dissipation only in spring. The phenological and structural characteristics of C. albidus protect it from excessive light loads, and reduce the need for investment in physiological mechanisms to avoid their harmful effects. Quercus ilex lacks such protection, and relies essentially on increased and sustained photodissipative activity at the physiological level.
Keywords: chlorophyll fluorescence; Cistus albidus L.

Improving the use of lichens as biomonitors of atmospheric metal pollution. - Branquinho, C; Catarino, F; Brown, D H; Pereira, M J; Soares, A (The Science of the total environment, 1999)
The data reported on this study supported the hypothesis that the absence of the lichen Ramalina fastigiata near a copper mine site located on the south of Portugal was related to toxic levels of Cu-dust near the centre of the mine. Lichen biodiversity reflected the impact of the copper-mine dust emissions which were more widespread towards the east, correlated with wind direction and frequency. The chemical analysis of R. fastigiata collected at different distances and in different directions from the mine showed that Cu, K and Mg were derived from the centre of the mine site, confirming thus as the major source of atmospheric dust. Total inhibition of PSII photochemical reactions occurred in R. fastigiata both under field and controlled conditions, when intracellular Cu concentrations exceeded a threshold of approximately 2.0 mumol g-1. No samples of this species were found under field conditions beyond the Cu threshold. Thus, the fluorescence parameter Fv/Fm proved to be a good estimator of the survival capacity of R. fastigiata under field conditions and thus a useful parameter in determining the sensitivity of the lichens (photobiont) to Cu pollution. The intracellular location of Cu allowed an explanation of the physiological changes and the survival of the species in the surroundings of the copper-mine.
Keywords: Atmospheric dust pollution; Cellular location of Cu; chlorophyll fluorescence; Cu-mine; Fv Fm; Intracellular Cu; K and Mg; Lichen biodiversity; lichens; Ramalina fastigiata

Improving the use of lichens as biomonitors of atmospheric metal pollution. - Branquinho, C.; Catarino, F.; Brown, D. H.; Pereira, M. J.; Soares, A. (The Science of the total environment, 1999)
The data reported on this study supported the hypothesis that the absence of the lichen Ramalina fastigiata near a copper mine site located on the south of Portugal was related to toxic levels of Cu-dust near the centre of the mine. Lichen biodiversity reflected the impact of the copper-mine dust emissions which were more widespread towards the east, correlated with wind direction and frequency. The chemical analysis of R. fastigiata collected at different distances and in different directions from the mine showed that Cu, K and Mg were derived from the centre of the mine site, confirming thus as the major source of atmospheric dust. Total inhibition of PSII photochemical reactions occurred in R. fastigiata both under field and controlled conditions, when intracellular Cu concentrations exceeded a threshold of approximately 2.0 mumol g-1. No samples of this species were found under field conditions beyond the Cu threshold. Thus, the fluorescence parameter Fv/Fm proved to be a good estimator of the survival capacity of R. fastigiata under field conditions and thus a useful parameter in determining the sensitivity of the lichens (photobiont) to Cu pollution. The intracellular location of Cu allowed an explanation of the physiological changes and the survival of the species in the surroundings of the copper-mine.
The following values have no corresponding Zotero field: accession-num: 10474262
Keywords: Atmospheric dust pollution; Cellular location of Cu; chlorophyll fluorescence; Cu-mine; Fv Fm; Intracellular Cu; K and Mg; Lichen biodiversity; lichens; Ramalina fastigiata

Photosynthesis and photoprotection in Quercus ilex resprouts after fire - Fleck, I; Hogan, K P; Llorens, L; Abadía, A; Aranda, X (Tree Physiology, 1998)
Plants that resprout after fires often have higher rates of photosynthesis than before a fire. To elucidate the mechanism of this response, we studied gas exchange and chlorophyll fluorescence in Quercus ilex L. plants growing on control (unburned) sites and on sites that had been burned the preceding summer. In early July, photosynthetic rates and stomatal conductance were similar in plants on unburned and burned plots, and in young and old foliage within unburned plots. At this time, photochemical efficiency of photosystem II (PSII), nonphotochemical quenching of chlorophyll fluorescence (NPQ), and the de-epoxidation of violaxanthin to zeaxanthin were also similar among leaves of different ages and treatments. In late July, photosynthetic rates and stomatal conductances were much greater in resprouts on the burned areas than in unburned plants. From early to late July, unburned plants showed an increase in NPQ and the de-epoxidation of violaxanthin to zeaxanthin, indicating increased photoprotection as a result of enhanced nonradiative dissipation of excess light energy. Plants on the burned plots did not show these changes. Leaves of all ages and treatments showed no substantial reduction in potential quantum yield of PSII (Fv/Fm) at midday or predawn, indicating that there was little or no photoinhibition. Leaf nitrogen and soluble protein contents varied with leaf age during July, but did not vary between treatments. We conclude that the primary effect of burning is an increase in water availability to resprouting plants that eliminates the need for photoprotection, at least in the short term. The decrease in photosynthetic rates of unburned leaves in late July was the result of reduced stomatal conductance. We suggest that lowered stomatal conductance is the primary limiting factor in Q. ilex leaves, governing the regulation of carboxylation activity and energy dissipation processes.
10.1093/treephys/18.8-9.607
Keywords: chlorophyll fluorescence; Gas exchange; Holm oak; photoinhibition; Photosystem II; zeaxanthin

Seasonal changes in xanthophyll composition and photosynthesis of cork oak (Quercus suber L.) leaves under mediterranean climate - García-Plazaola, J. I.; FARIA, T.; Abadía, J.; Chaves, M. M.; Pereira, J. S. (Journal of Experimental Botany, 1997)
Seasonal changes in pigment composition of sun and shade leaves of cork oak (Quercus suber) were studied under field conditions in Portugal. Expanding leaves showed a high concentration of xanthophyll cycle components, violaxanthin, antheraxanthin and zeaxanthin. The pool of violaxanthin plus antheraxanthin plus zeaxanthin (V+A+Z) varied greatly between the seasons, being higher at the end of summer and in winter when photosynthesis was limited by water stress and cold, respectively. The size of V+A+Z pool was associated to synthesis of zeaxanthin in response to an excess of light. In sun leaves, midday A+Z relative content was positively correlated with the V+A+Z pool, whereas in shade leaves A+Z decreased with leaf ageing. In both leaf types A+Z was positively correlated with the non-photochemical quenching (NPQ) of chlorophyll a fluorescence. However, in winter NPQ did not change significantly throughout the day, whereas the (A+Z)/(V+A+Z) increased following the typical daily trend observed in other seasons.
10.1093/jxb/48.9.166710.1093/jxb/48.9.1667
Keywords: chlorophyll fluorescence; pigments; Quercus suber; thermal dissipation; xanthophylls

Seasonal changes in xanthophyll composition and photosynthesis of cork oak (Quercus suber L.) leaves under mediterranean climate - Garcia-Plazaola, J I; Faria, T; Abadia, J; Chaves, M M; Pereira, J S (Journal of Experimental Botany, 1997)
Seasonal changes in pigment composition of sun and shade leaves of cork oak (Quercus suber) were studied under field conditions in Portugal. Expanding leaves showed a high concentration of xanthophyll cycle components, violaxanthin, antheraxanthin and zeaxanthin. The pool of violaxanthin plus antheraxanthin plus zeaxanthin (V+A+Z) varied greatly between the seasons, being higher at the end of summer and in winter when photosynthesis was limited by water stress and cold, respectively. The size of V+A+Z pool was associated to synthesis of zeaxanthin in response to an excess of light. In sun leaves, midday A+Z relative content was positively correlated with the V+A+Z pool, whereas in shade leaves A+Z decreased with leaf ageing. In both leaf types A+Z was positively correlated with the non-photochemical quenching (NPQ) of chlorophyll a fluorescence. However, in winter NPQ did not change significantly throughout the day, whereas the (A+Z)/(V+A+Z) increased following the typical daily trend observed in other seasons.
10.1093/jxb/48.9.1667
Keywords: chlorophyll fluorescence; pigments; Quercus suber; thermal dissipation; xanthophylls

Limitation of photosynthetic activity by CO2 availability in the chloroplasts of oak leaves from different species and during drought - Roupsard, O.; Gross, P.; Dreyer, E. (Ann. For. Sci., 1996)
It has recently been suggested that the low photosynthesis rates in tree species as compared to highly productive crops is at least partly due to resistances opposing the CO 2 fluxes in the mesophyll of tree leaves. To validate this assertion, values of CO2 mole fractions in the chloroplasts of leaves from Quercus petraea, Q robur, Q ilex and Populus sp were estimated on the basis of the analysis of the partitioning of light driven electron flow between fractions used for the carboxylation or the oxygenation of RuBP by Rubisco. The procedure used included: i) a measure of total light driven electron flows derived from the chlorophyll a fluorescence ratio ΔF/Fm', which is proportional to the photochemical efficiency of PS II, multiplied by incident irradiance and a calibration coefficient; ii) an estimation of the electron flux devoted to carboxylation obtained from net CO2 assimilation and respiration rate measurement, and using the known electron requirements (four electrons for CO2 or O2 fixation); iii) the derivation of the CO2 mole fraction in the chloroplasts from the specificity factor of Rubisco, and the ratio of carboxylation/oxygenation of RuBP. Results showed that in the absence of drought stress, the mole fraction of CO2 in the chloroplasts (35-45% of the atmospheric one) was much lower than the calculated substomatal one (60-70% of the atmospheric) in all species. Moreover, lowest values were recorded in the species with lowest assimilation rates, suggesting that the differences in the net CO 2 assimilation rate between species are linked to the CO2 availability in the chloroplasts. Finally, the CO2 availability decreased with increasing drought in the soil, stressing the importance of reduced influx of CO2 as an important factor for drought-induced declines of photosynthesis. These results are discussed with respect to the occurrence of significant resistances in the leaf mesophyll, in addition to the stomatal resistances.
Keywords: chlorophyll fluorescence; chloroplasts; CO2 diffusion; Drought; mesophyll conductance; oaks; Stomatal conductance

Limitation of photosynthetic activity by CO2 availability in the chloroplasts of oak leaves from different species and during drought - Roupsard, O; Gross, P; Dreyer, E (Ann. For. Sci., 1996)
It has recently been suggested that the low photosynthesis rates in tree species as compared to highly productive crops is at least partly due to resistances opposing the CO 2 fluxes in the mesophyll of tree leaves. To validate this assertion, values of CO2 mole fractions in the chloroplasts of leaves from Quercus petraea, Q robur, Q ilex and Populus sp were estimated on the basis of the analysis of the partitioning of light driven electron flow between fractions used for the carboxylation or the oxygenation of RuBP by Rubisco. The procedure used included: i) a measure of total light driven electron flows derived from the chlorophyll a fluorescence ratio ΔF/Fm', which is proportional to the photochemical efficiency of PS II, multiplied by incident irradiance and a calibration coefficient; ii) an estimation of the electron flux devoted to carboxylation obtained from net CO2 assimilation and respiration rate measurement, and using the known electron requirements (four electrons for CO2 or O2 fixation); iii) the derivation of the CO2 mole fraction in the chloroplasts from the specificity factor of Rubisco, and the ratio of carboxylation/oxygenation of RuBP. Results showed that in the absence of drought stress, the mole fraction of CO2 in the chloroplasts (35-45% of the atmospheric one) was much lower than the calculated substomatal one (60-70% of the atmospheric) in all species. Moreover, lowest values were recorded in the species with lowest assimilation rates, suggesting that the differences in the net CO 2 assimilation rate between species are linked to the CO2 availability in the chloroplasts. Finally, the CO2 availability decreased with increasing drought in the soil, stressing the importance of reduced influx of CO2 as an important factor for drought-induced declines of photosynthesis. These results are discussed with respect to the occurrence of significant resistances in the leaf mesophyll, in addition to the stomatal resistances.
Keywords: chlorophyll fluorescence; chloroplasts; CO2 diffusion; Drought; mesophyll conductance; oaks; Stomatal conductance

Seasonal courses of photosynthetic activity and sublethal temperature tolerance of Quercus ilex leaves - Méthy, M; Trabaud, L (Forest Ecology and Management, 1993)
The reaction of the photosynthetic system of a sclerophyllous tree of the Mediterranean region (Quercus ilex) to three temperature levels (one ambient and two sublethal) was analysed monthly for 1 year. Measurements were carried out on leaves less than 3 months old as well as on leaves older than 3 months by laser-induced chlorophyll fluorescence. Treatments were: control (unheated), 50°C for 30 min, and 60°C 10 min. Both for unheated and treated leaves the vitality index shows a seasonal course depending on the treatments. At 50°C the photosynthetic apparatus of leaves of the two ages is moderately affected. At 60°C the apparatus is severely damaged whatever the season and is unable to recover. The consequences for the management of Q. ilex forests in relation to some thermal stresses are considered.
Keywords: chlorophyll fluorescence; leaves; photosynthetic apparatus; Quercus ilex (PG); thermal stress

Caractérisation de la résistance au froid de deux espèces sclérophylles méditerranéennes par la fluorescence de la chlorophylle - Méthy, M; Trabaud, L (Ann. For. Sci., 1990)
Frost resistance characterisation of two mediterranean sclerophyllous species by chlorophyll fluorescence. Frost resistance of the photosynthetic system of 2 sclerophyllous species of the mediterranean region, Quercus ilex and Quercus coccifera, has been analysed. Measurements were made on 1 year and 1 month old leaves by the chlorophyll fluorescence induction method. Photosynthetic activity is inhibited very quickly for both the 2 species at the development stages studied. The photosynthetic system of Q ilex seems to be the most resistant but is destroyed after half an hour of exposure to cold at -20 °C, without any recovery after treatment. The effect of winter temperatures on the distribution areas of Q ilex and Q coccifera is discussed.
Keywords: chlorophyll fluorescence; Freezing; Quercus coccifera; Quercus ilex; Sclerophyll